Construction and immune efficacy of recombinant Lactobacillus casei expressing OmpAI of Aeromonas veronii C5–I as molecular adjuvant. (July 2021) - Lin-Zhao, Ze; Tong-Yang, Bin; Yi-Xuan, Yang; Ning-Guo, Song; Xing-Zhang, Dong; Nan-Ji, Sheng; Lv, Bing; Huan-Kang, Yuan; Feng-Shan, Xiao; Mei-Shi, Qiu; Wen-Sun, Wu; Dong-Qian, Ai
Abstract: Despite advancements in diagnosis and control, Aeromonas infections are considered the leading cause of economic aquaculture loss. In this study, to enhance DNA vaccine efficacy against Aeromonas infections, a fused DNA fragment (1504 bp) of the OmpAI gene from Aeromonas veronii ( A. veronii ) combined with the C5–I gene from the common carp was generated with splicing by overlapping PCR (SOE-PCR) and expressed in Lactobacillus casei strain CC16. Protein C5–I served as a molecular adjuvant for the antigen OmpAI. Two types of fusion antigens were developed (anchored and secretory). Generally, anchored-type antigens are more effective in inducing immune responses in fish than secretory antigens. Western blot analysis showed that the bands of both antigens were present at 58 kDa. After oral immunization, both DNA vaccines enhanced the serum levels of AKP, ACP, SOD and LZM in immunized carp; the genes IL-10, IL-1β, TNF-α, and IFN-γ in the heart, liver, spleen, head kidney, and intestinal tract were upregulated; and a stronger phagocytic response was triggered in immunized fish. In addition, common carp administered the fused antigens were more protected from Aeromonas challenge (60–73.3% protection). Recombinant Lactobacillus bacteria expressing the fused protein showed a greater propensity for colonization in the intestinal tract in immunized fish than in controls. Here, we provide a promising approach to improve DNA vaccine immunogenicity for protecting common carp from A. veronii infections. Highlights: Two kinds of recombinant L.casei were constructed by using common carps complement C5–I gene as the molecular adjuvant of OmpAI gene of Aeromonas veronii strain TH0426. The expression level of IgM, IL-10, IL-β, IFN-γ, TNF-α and activity of ACP, AKP, LZM and SOD of immune fish can be improved by adding molecular adjuvant. The serum of fish that received recombinant L. casei exhibited increase leukocytes phagocytosis ability. Adding molecular adjuvant can improve the protection rate of recombinant L.casei for crucian carps against A. veronii.